366 Micro-Endoscopic Posterior Cervical Foraminotomy and Discectomy is Health Economically Dominant to Anterior Cervical Discectomy and Fusion for Unilateral Cervical Radiculopathy. (April 2023) - Hani, Ummey; Monk, Steve Hubert; Pfortmiller, Deborah; Kim, Paul Keetae; Bohl, Michael; Holland, Christopher Michael; Smith, Mark D.; Adamson, Tim E.; McGirt, Matthew J.
Abstract : INTRODUCTION: Micro-endoscopic posterior cervical foraminotomy and discectomy (MPCF) has served as a minimally invasive, motion sparing alternative to ACDF for unilateral cervical radiculopathy for decades. While growing data suggests similar effectiveness, the cost effectiveness and potentially superior healthcare value of MPCF vs ACDF remains largely unstudied. METHODS: The National Quality Outcomes Database (QOD) was queried for 323 consecutive ASA 1-3 patients (201 ACDF, 122 MPCF) performed at the authors' single institution for unilateral cervical radiculopathy at our ambulatory surgical center (ASC). Propensity-matching yielded 222 patients. Resource utilization, missed workdays, and EQ5D quality adjusted life year (QALY) gains were assessed over a one-year period. Direct cost (resource use x unit costs based on Medicare national allowable payment amounts) and indirect cost (missed workdays x average US daily wage) were recorded and incremental cost-effectiveness ratio (ICER) was calculated. RESULTS: Estimated blood loss, and length of surgery were less for MPCF vs. ACDF (p < 0.001). All other safety measures and patient-reported outcomes were similar between cohorts. MPCF vs. ACDF demonstrated reduction in total one-year costs of $6, 709 (Medicare) and $13, 061 (private payers) (p < 0.001), and comparable QALYs gained. ACDF vs. MPCF had a cost ineffective ICER of $91, 773/QALY-gained and $178, 668/QALY for Medicare and private payer patients, respectively. CONCLUSIONS: MPCF is a health-economically dominant option to ACDF for unilateral cervical radiculopathy given the increased healthcare costs despite comparable safety, outcome, and QALY gains associated with ACDF.